Relational Care for Perinatal Substance Use. Issue 5 (September 2015) - Kramlich, Debra; Kronk, Rebecca
Abstract Objective: The purpose of this systematic review of the literature is to highlight published studies of perinatal substance use disorder that address relational aspects of various care delivery models to identify opportunities for future studies in this area. Method: Quantitative, qualitative, and mixed-methods studies that included relational variables, such as healthcare provider engagement with pregnant women and facilitation of maternal–infant bonding, were identified using PubMed, Scopus, and EBSCO databases. Key words included neonatal abstinence syndrome, drug, opioid, substance, dependence, and pregnancy. Results: Six studies included in this review identified statistically and/or clinically significant positive maternal and neonatal outcomes thought to be linked to engagement in antenatal care and development of caring relationships with healthcare providers. Implications/Conclusion: Comprehensive, integrated multidisciplinary services for pregnant women with substance use disorder aimed at harm reduction are showing positive results. Evidence exists that pregnant women's engagement with comprehensive services facilitated by caring relationships with healthcare providers may improve perinatal outcomes. Gaps in the literature remain; studies have yet to identify the relative contribution of multiple risk factors to adverse outcomes as well as program components most likely to improve outcomes.